Molecular Interactions of Pyrazine-Based Compounds to Proteins - Juhás, Martin; Zitko, Jan (Journal of medicinal chemistry, 2020)
Pyrazine-based compounds are of great importance in medicinal chemistry. Due to their heteroaromatic nature, they uniquely combine properties of heteroatoms (polar interactions) with the properties of aromatic moieties (nonpolar interactions). This review summarizes results of a systematic analysis of RCSB PDB database focused on important binding interactions of pyrazine-based ligands cocrystallized in protein targets. The most frequent interaction of pyrazine was hydrogen bond to pyrazine nitrogen atom as an acceptor, followed by weak hydrogen bond with pyrazine hydrogen as donor. We also identified intramolecular hydrogen bonds within pyrazine ligands, π-interactions, coordination to metal ions, and few halogen bonds in chloropyrazines. In many cases the binding mode of the pyrazine fragment was complex, involving a combination of several interactions. We conclude that pyrazine as a molecular fragment should not be perceived as a simple aromatic isostere but rather as a readily interacting moiety of drug-like molecules with high potential for interactions to proteins.
Keywords: Molecular Dynamics Simulation; databáze proteinů; vodíková vazba; vazebná místa; pyraziny; Metals; Pyrazines; Amino Acyl-tRNA Synthetases; lidé; simulace molekulární dynamiky; kovy; Proteins; Ligands; aminoacyl-tRNA-synthetasy; proteiny; Databases, Protein; Hydrogen Bonding; ligandy; Binding Sites; Humans